A bioprocess optimization study to enhance the production of Menaquinone-7 using Bacillus subtilis MM26 - Maneesha M; Subathra Devi C (Microbial Cell Factories)
Abstract Background Menaquinone-7 (MK-7) has a vital significance in promoting human health and tackling several global health concerns which makes its production extremely important. MK-7 is not easily accessible at a reasonable cost due to the poor fermentation yields and the existence of several laborious downstream unit processes. Efficient manufacturing methods are essential to meet the global requirements due to the increasing demand in the pharmaceutical and nutraceutical industries. This research study focuses on the enhanced production of MK-7 from Bacillus subtilis MM26 isolated from fermented home-made wine. Results A suitable MK-7 production medium for Bacillus subtilis MM26 was determined and the yield was found to be 67 ± 0.6 mg/L. The one factor at a time (OFAT) results showed that medium containing lactose, glycine, with a pH 7, a temperature of 37 °C, and an inoculum size of 2.5% (2 × 10⁶ CFU/mL) was optimal synthesis of MK-7. RSM indicated that incubation time, carbon and nitrogen sources were the factors significantly affecting the MK-7 yield. RSM predicted optimal conditions, which yielded a maximum concentration of 442 ± 2.08 mg/L of MK-7. Conclusions The outcomes of this study demonstrated the potential of Bacillus subtilis MM26 in large-scale industrial production of MK-7. The yield of MK-7 was amplified efficiently by integration of OFAT and RSM, paving the way for cost-efficient industrial production.